HOSPITAL SERVICE ETHICS AND CULTURE: PATIENT AND EMPLOYEE SAFETY PROTECTION BASED ON THE CODE OF ETHICS, CULTURAL VALUES, AND HEALTH LAWS – LITERATURE REVIEW - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2025)
This study aims to examine the role of hospital service ethics and culture in protecting patient and employee safety based on professional codes of ethics, organisational cultural values, and applicable health regulations. Using a Systematic Literature Review approach, this study examines various national and international literature from the last ten years related to patient safety, safety culture, and health worker protection. The results of the study show that patient safety is greatly influenced by the application of professional ethical principles, particularly in respecting patient rights, implementing informed consent, and organisational culture that encourages transparency, communication, and incident reporting. On the other hand, the protection of hospital employees is closely related to a healthy organisational culture, ethical leadership, and the implementation of labour and occupational health regulations to ensure physical and psychological safety. The integration of ethics, culture, and law was found to be the main strategy capable of bridging the gap between theory and practice in the field. This study emphasises that strengthening hospital management's commitment to the code of ethics, internalising a culture of safety, and complying with health laws are the foundations for creating a safe, fair, and sustainable service environment for both patients and employees.